2016
DOI: 10.4269/ajtmh.16-0204
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax Landscape in Brazil: Scenario and Challenges

Abstract: Brazil is the largest country of Latin America, with a considerable portion of its territoritory within the malaria-endemic Amazon region in the North. Furthermore, a considerable portion of its territory is located within the Amazon region in the north. As a result, Brazil has reported half of the total malaria cases in the Americas in the last four decades. Recent progress in malaria control has been accompanied by an increasing proportion of Plasmodium vivax, underscoring a need for a better understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 55 publications
0
57
0
4
Order By: Relevance
“…Analysis of this mitochondrial genome sequence revealed that all four samples shared identical sequences, and these were identical to the mitochondrial genome sequence of P. simium available at genbank, which differs from the most closely related isolates of P. vivax by two unique P. simium-specific SNPs. Analysis of 794 full-length mitochondrial genome sequences from globally acquired P. vivax samples [1][2][3][4][5][6][7] confirmed that these SNPs were unique to P. simium. A haplotype network tree ( Figure 3) was constructed using these sequences, and clearly shows that P. simium is most closely related to the P. vivax parasites of man isolated from South America.…”
Section: Molecular Characterizationmentioning
confidence: 88%
See 1 more Smart Citation
“…Analysis of this mitochondrial genome sequence revealed that all four samples shared identical sequences, and these were identical to the mitochondrial genome sequence of P. simium available at genbank, which differs from the most closely related isolates of P. vivax by two unique P. simium-specific SNPs. Analysis of 794 full-length mitochondrial genome sequences from globally acquired P. vivax samples [1][2][3][4][5][6][7] confirmed that these SNPs were unique to P. simium. A haplotype network tree ( Figure 3) was constructed using these sequences, and clearly shows that P. simium is most closely related to the P. vivax parasites of man isolated from South America.…”
Section: Molecular Characterizationmentioning
confidence: 88%
“…However, there are a consistent number of autochthonous cases reported in southern and southeastern Brazil; regions from where human malaria was eliminated 50 years ago. 2 Most of these episodes are attributed to P. vivax, predominantly occur in areas of dense Atlantic forest vegetation, and mainly affect non-resident visitors. In most outbreaks, there is no identifiable index case that could have introduced the parasite from a malaria endemic region.…”
Section: Introductionmentioning
confidence: 99%
“…This regional, or subregional, surveillance system may provide a timely alert on variations of malaria epidemiology or emergence of antimalarial drug resistance. Although the risk of emergence of resistant P. falciparum has been the main concern until now, the increasing proportion of P. vivax cases leads to other challenges: the control of hypnozoites with the prevention of relapses and the emergence of choloroquine-resistant P. vivax [, [64][65][66]. The role of tafenoquine for hard-to-reach populations could be discussed for future strategies [67,68].…”
Section: Importance Of Cooperative Regional Monitoring and Responsementioning
confidence: 99%
“…In response, the National Program for Malaria Control was launched, focusing on early diagnosis and treatment through an increased number of local health care facilities. At the time, infections with P. falciparum and P. vivax displayed similar rates, and the program soon led to reduction of P. falciparum cases, even though the total number of cases remained relatively high [5,7,11,14,15].…”
mentioning
confidence: 99%